IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA PADA SEKOLAH ADAB INSAN MULIA DEPOK MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Nurul, Fadia (PT Triputra Sejahtera Prima, 2024)
Education is a fundamental right that must be fulfilled to ensure the creation of quality human development. However, in Indonesia, the issue of school dropouts remains a serious problem, primarily due to the financial challenges faced by students. Scholarships are an important solution to provide financial support to students with potential who are hindered by economic difficulties. Sekolah Adab Insan Mulia Depok is one of the institutions that offers scholarship programs for students facing financial challenges. However, the current scholarship selection process is still subjective, which can lead to unfair distribution. To address this issue, it is necessary to shift from subjective to objective selection methods using a Decision Support System (DSS). This study proposes the use of the Weighted Product (WP) method as a solution to improve the scholarship selection process at the school. The WP method was chosen because it can process data by considering the relative weight of each criterion used. With this system, the selection process becomes more accurate, objective, and transparent. The implementation of the WP method in the DSS can generate student rankings based on scores calculated systematically, allowing for a more equitable and targeted distribution of scholarships, according to the financial needs and achievements of the students.